2012
DOI: 10.1155/2012/953910
|View full text |Cite
|
Sign up to set email alerts
|

An Acute Case of Herpes Zoster Ophthalmicus with Ophthalmoplegia

Abstract: Herpes zoster ophthalmicus (HZO) with oculomotor nerve involvement is rare, even rarer as an acute presentation rather than sequelae of HZO. In this paper we present a case of cutaneous HZO in which our patient's initial presentation was one of complete ophthalmoplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The third oculomotor nerve is most commonly affected, followed by the abducens nerve and the trochlear nerve [ 15 ]. Ophthalmoplegia was also reported [ 14 ],[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third oculomotor nerve is most commonly affected, followed by the abducens nerve and the trochlear nerve [ 15 ]. Ophthalmoplegia was also reported [ 14 ],[ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include direct viral cytopathic effect,[ 4 ] reactive immune-related response,[ 4 ] microinfarction secondary to vascular inflammation[ 5 ] or direct compression due to the soft tissue swelling and inflammation at the orbital apex. [ 6 ] Multiple concurrent pathologic mechanisms including ischemia leading to microinfarction might have been responsible for such manifestations with almost no recovery like in our case. Interestingly, almost 90% of the patients with VZV-related ophthalmoplegia disclose evidence of aseptic meningitis, as seen with our patient.…”
Section: Discussionmentioning
confidence: 73%
“…HZO is known to occur more frequently in patients with immunosuppression. [ 8 ] Despite a few anecdotal reports,[ 1 3 6 9 ] it has not been proven conclusively that OAS secondary to HZO occurs more commonly in immune deficient patients. It has been suggested that early treatment with antivirals has a better outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Acute ophthalmoplegia appearing within the first days of disease presentation is rare. 20 , 21 It was reported that ptosis and ophthalmoplegia caused by HZ appeared to be self-limiting. However, in some patients, residual ptosis and/or limited ocular motility can last indefinitely.…”
Section: Discussionmentioning
confidence: 99%